Carbon-Based Flexible and All-Solid-State Micro-supercapacitors Fabricated by Inkjet Printing with Enhanced Performance - Pei, Zhibin; Hu, Haibo; Liang, Guojin; Ye, Changhui (Nano-Micro Letters, 2016)
By means of inkjet printing technique, flexible and all-solid-state micro-supercapacitors (MSCs) were fabricated with carbon-based hybrid ink composed of graphene oxide (GO, 98.0 vol.%) ink and commercial pen ink (2.0 vol.%). A small amount of commercial pen ink was added to effectively reduce the agglomeration of the GO sheets during solvent evaporation and the following reduction processes in which the presence of graphite carbon nanoparticles served as nano-spacer to separate GO sheets. The printed device fabricated using the hybrid ink, combined with the binder-free microelectrodes and interdigital microelectrode configuration, exhibits nearly 780% enhancement in areal capacitance compared with that of pure GO ink. It also shows excellent flexibility and cycling stability with nearly 100% retention of the areal capacitance after 10,000 cycles. The all-solid-state device can be optionally connected in series or in parallel to meet the voltage and capacity requirements for a given application. This work demonstrates a promising future of the carbon-based hybrid ink for directly large-scale inkjet printing MSCs for disposable energy storage devices. Highlights: 1 Flexible and all-solid-state micro-supercapacitors (MSCs) were fabricated by inkjet printing using carbon-based hybrid ink composed of graphene oxide (GO) and commercial pen ink. 2 The as-obtained MSCs based on hybrid ink exhibit great enhancement in areal capacitance, flexibility and cycling stability compared with that of pure GO ink. 3 This work provides a promising strategy for large-scale preparation of low-cost, lightweight, and flexible/wearable energy storage devices with carbon-based hybrid ink.